2011
DOI: 10.1177/2041297510393584
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and mechanical properties of Al2O3/AZ91 surface nanocomposite layer produced by friction stir processing

Abstract: In this paper, the effects of friction stir processing (FSP) parameters on the mechanical properties and microstructures of as-cast magnesium AZ91 alloy are investigated. Grain-growth and microhardness of friction-stir-processed specimens with and without nano-sized aluminium oxide (Al2O3) particles are compared. The effects of process parameters on tunnelling cavity and other friction stir processing defects are discussed. The paper describes the proper process parameters under which a uniform distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…FSW is considered as a solid-state process in which the base materials are placed next to each other and then a non-consumable tool comprising shoulder and pin is placed at the center of the joint line. 2527 Then, the joint is created due to heat generated by shoulder and stirring of plasticized materials by rotation of the tool pin with its traverse movement. 2830 A schematic view of the FSW process for dissimilar joint of Al alloys is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…FSW is considered as a solid-state process in which the base materials are placed next to each other and then a non-consumable tool comprising shoulder and pin is placed at the center of the joint line. 2527 Then, the joint is created due to heat generated by shoulder and stirring of plasticized materials by rotation of the tool pin with its traverse movement. 2830 A schematic view of the FSW process for dissimilar joint of Al alloys is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, adding powders to the HDPE matrix would reduce chain mobility, which caused a decrease in tensile strength. The reduction in the composite materials in tensile strength can also be explained by the model 26…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the transverse speed would decrease the maximum temperature and the amount of molten material inside the processed zone but increase the heating and cooling rates. 26 It led to the formation of a large number of voids ( Figure 5(e)). When the transverse speed was too high (90 mm/min), there would be high heterogeneity in the processed zone ( Figure 5(f)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical and scanning electron micrographs shows a uniform distribution of needle shape Al 3 Zr particles in the aluminum matrix. G Faraji et al [12] found the effects of friction stir processing (FSP) parameters on the mechanical properties and microstructures of as-cast magnesium AZ91 alloy and also compared Grain growth and microhardness of friction-stir-processed specimens with and without nano-sized aluminium oxide (Al 2 O 3 ) particles. Yong X. Gan et al [13] did a review of friction stir processing (FSP) technology and its application for microstructure modification of particle reinforced composite materials.M.Puviyarasan et al [14] applied Friction Stir Processing (FSP) a recent grain refinement technique to disperse micron-sized (2µm) SiCp particles into aluminum alloy AA6063.…”
Section: Introductionmentioning
confidence: 99%